THE PROSPECT OF INTERPLANETARY MISSION: ARE WE READY? - Taufik Rachmat Nugraha (Padjadjaran Journal of International Law, 2022)
Mars exploration missions in the future will be focused on Mars Sample Return (MSR) and humans as space crew in late 2028 or early 2030 by NASA and other non-government entities, such as Space Exploration Technologies (Space X) and Blue Origin. MSR and sending humans to explore Mars raises environmental contamination issues, which are governed in law by Article IX of the Outer Space Treaty 1968 to “avoid harmful contamination.” Though there is no existing international law instrument to address this issue comprehensively, Article IX was not clear to explain harmful contamination. Thus, non-governmental entities involved in future missions to Mars face liability, especially in the case of an accident causing fatalities or adverse environmental impact for the Earth and Mars. This article examines related regulations in corpus iuris spatialis, including soft law and elaborating with astrobiological data to encourage new regulation, ensuring liability and environmental safety on future Mars missions.